2023
DOI: 10.1038/s41598-023-34021-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oxidative stress-related genes differentially expressed in Alzheimer’s disease and construction of a hub gene-based diagnostic model

Abstract: Alzheimer’s disease (AD) is the most prevalent dementia disorder globally, and there are still no effective interventions for slowing or stopping the underlying pathogenic mechanisms. There is strong evidence implicating neural oxidative stress (OS) and ensuing neuroinflammation in the progressive neurodegeneration observed in the AD brain both during and prior to symptom emergence. Thus, OS-related biomarkers may be valuable for prognosis and provide clues to therapeutic targets during the early presymptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Moreover, in longitudinal studies, either the number of samples has been low, thus limiting the depth of the analysis, or the tissues considered have not been brain-derived. In any case, the previous studies enabled us to identify not only relevant pathways associated with AD pathology but also gene candidates that can drive the pathology or be employed as biomarkers (Hu et al, 2020; Miller et al, 2008; Soleimani Zakeri et al, 2020; Sun et al, 2022; Upadhyaya et al, 2020; Zhang and Kiryu, 2023). Here, the dataset employed provided transcriptomic data of early, intermediate and late AD stages identified via integration of several pathological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in longitudinal studies, either the number of samples has been low, thus limiting the depth of the analysis, or the tissues considered have not been brain-derived. In any case, the previous studies enabled us to identify not only relevant pathways associated with AD pathology but also gene candidates that can drive the pathology or be employed as biomarkers (Hu et al, 2020; Miller et al, 2008; Soleimani Zakeri et al, 2020; Sun et al, 2022; Upadhyaya et al, 2020; Zhang and Kiryu, 2023). Here, the dataset employed provided transcriptomic data of early, intermediate and late AD stages identified via integration of several pathological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…27 Gene expression mapping in AD patients showed a profile highly associated with oxidative stress, with genes related to immune exhaustion, damage to transcription factors and mutations in genes promoting protective responses. 28 It has been reported that rats with depressive-like behaviours induced by Aβ have decreased levels of serotonin (5-HT) and norepinephrine (NA) and, in contrast, increased levels of tryptophan (TRP) and kynurenine (KYN) and high concentrations of ROS in the PFC, and consequent establishment of a neuroinflammatory state with local tissue damage (Figure 2). Pharmacotherapy aimed at inhibiting IDO has demonstrated efficacy in controlling depression, reversing 5-HT levels and oxidative stress in animal models exposed to the accumulation of amyloid-β protein.…”
Section: Oxidative Stress and Amyloid-β Proteinmentioning
confidence: 99%
“…Imaging methods showed increased oxidative damage due to Aβ deposition associated with lower glutathione and superoxide dismutase (SOD) activity in a mice model to study AD 27 . Gene expression mapping in AD patients showed a profile highly associated with oxidative stress, with genes related to immune exhaustion, damage to transcription factors and mutations in genes promoting protective responses 28 …”
Section: Oxidative Stress and Amyloid‐β Proteinmentioning
confidence: 99%
“…The production of ROS can be significantly increased by several pathogenic conditions, including inflammation, metal dyshomeostasis, and mitochondrial dysfunction by various environmental traumas (such as infections, UV, or heat exposure). , This condition is cumulatively called as oxidative stress. , Oxidative stress is a state of imbalance between the production of reactive oxygen/nitrogen species (ROS/RNS) and the capacity of antioxidants to remove these toxic species from the body. Increased oxidative stress is thought to be linked to one of the earliest steps in the onset of neurodegeneration in AD. , Therefore, molecules exhibiting promising antioxidant properties are supposed to offer hope against AD, where free radicals play a key role in the disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Increased oxidative stress is thought to be linked to one of the earliest steps in the onset of neurodegeneration in AD. 20,21 Therefore, molecules exhibiting promising antioxidant properties are supposed to offer hope against AD, where free radicals play a key role in the disease progression.…”
Section: Introductionmentioning
confidence: 99%